EFFECTS OF DRILLING GENERATED HEAT ON DELAMINATION IN GLASS FIBER REINFORCED EPOXY (GFRE) COMPOSITES - Muhamad, Muhamad Fikri (IRC, 2016)
Fiber composites are widely used in aircraft, automobile and oil and gas due to their believed advantages. For the assembly purposes, drilling holes in composite is required for the material removal process. However, drilling fiber composites is very challenging because of several problems encountered during drilling; these are damage at holes interface and at the drilled hole walls. The aim of this research is to investigate the influence of drilling generated heat using various cutting speeds and feed rates on delamination in glass fiber reinforced epoxy (GFRE). GFRE composite was fabricated into a flat plate using hand lay-up technique.